Slurry-phase ethylene polymerisation using group 4 ansa-bridged permethylindenyl complexes supported on polymethylaluminoxane - Lamb, JV; Abell, JC; McLaren, JE; Buffet, J-C; Turner, ZR; O'Hare, D (Elsevier, 2019)
Five new group 4 ansa-bridged permethylindenyl complexes with either a dimethylsilane bridge or a tetramethyldisilane bridge have been synthesised and fully characterised. These complexes were supported on a hydrocarbon insoluble polymethylaluminoxane (sMAO) and their slurry-phase ethylene polymerisation performance was investigated. The highest activity was achieved using SBMe2(CpMe,I*)Zr(CH2SiMe3)2 (8042 kgPE molZr–1 h–1 bar–1 at 60 °C) but a decrease in activity was observed with an increase in the length of the bridge. DSC analysis of the polymers revealed the production of HDPE with minimal branching and defects, while SEM showed the production of polymer particles with commercially desirable uniform, ‘popcorn’, morphology. GPC analysis showed the production of polyethylenes with Mw < 570 kg mol–1 at 80 °C. In addition, SBMe2(Cp,I*)Zr(CH2SiMe3)2 was immobilised on MAO modified layered double hydroxide (LDHMAO). The slurry-phase polymerisation activity of SBMe2(Cp,I*)Zr(CH2SiMe3)2 on this support system was similar to the sMAO support; however, the polymer morphology was much less uniform.